Programmed death-1 expression on HIV-1-specific CD8+ T cells is shaped by epitope specificity, T-cell receptor clonotype usage and antigen load - Kløverpris, H; McGregor, R; McLaren, J; Ladell, K; Stryhn, A; Koofhethile, C; Brener, J; Chen, F; Riddell, L; Graziano, L; Klenerman, P; Leslie, A; et al. (Lippincott Williams and Wilkins, 2014)
Objectives: Although CD8+ T cells play a critical role in the control of HIV-1 infection, their antiviral efficacy can be limited by antigenic variation and immune exhaustion. The latter phenomenon is characterized by the upregulation of multiple inhibitory receptors, such as programmed death-1 (PD-1), CD244 and lymphocyte activation gene-3 (LAG-3), which modulate the functional capabilities of CD8+ T cells. Design and methods: Here, we used an array of different human leukocyte antigen (HLA)-B*15 : 03 and HLA-B*42 : 01 tetramers to characterize inhibitory receptor expression as a function of differentiation on HIV-1-specific CD8+ T-cell populations (n=128) spanning 11 different epitope targets. Results: Expression levels of PD-1, but not CD244 or LAG-3, varied substantially across epitope specificities both within and between individuals. Differential expression of PD-1 on T-cell receptor (TCR) clonotypes within individual HIV-1-specific CD8+ T-cell populations was also apparent, independent of clonal dominance hierarchies. Positive correlations were detected between PD-1 expression and plasma viral load, which were reinforced by stratification for epitope sequence stability and dictated by effector memory CD8+ T cells. Conclusion: Collectively, these data suggest that PD-1 expression on HIV-1-specific CD8+ T cells tracks antigen load at the level of epitope specificity and TCR clonotype usage. These findings are important because they provide evidence that PD-1 expression levels are influenced by peptide/HLA class I antigen exposure. © 2014 Wolters Kluwer Health.